Postretirement Life Satisfaction and Financial Vulnerability: The Moderating Role of Control. (14th September 2018) - Carr, Dawn C; Moen, Phyllis; Perry Jenkins, Maureen; Smyer, Michael
Abstract: Objectives: This article examines changes in life satisfaction around retirement exits for those with varying preretirement incomes, testing whether constraints on personal control and control over finances moderate the relationship between retiring and preretirement income. Method: This longitudinal study draws data from the 2004–2014 waves of the Health and Retirement Study to examine changes in life satisfaction pre- versus postretirement for three groups (the poor/near poor, financially vulnerable, and financially stable) of full-time workers aged 51–87 years ( N = 970), and a subset ( N = 334) who fully retire over a 4-year period. Results: Controlling for baseline life satisfaction, health, job/demographic characteristics, and social engagement, ordinary least squares regression results show financially stable retirees report higher levels of postretirement life satisfaction relative to their full-time working counterparts, whereas the poor/near poor and the financially vulnerable report similar life satisfaction to those who continue working full time. Constraints on personal control and control over finances moderate postretirement life satisfaction for the financially vulnerable. Discussion: Results suggest full retirement predicts improved life satisfaction only for those most advantaged financially. Financially vulnerable older workers may adjust more effectively to retirement if they have access to resources that facilitate greater control over their lives.